2019
DOI: 10.1111/epi.16357
|View full text |Cite
|
Sign up to set email alerts
|

Imaging biomarkers of posttraumatic epileptogenesis

Abstract: Traumatic brain injury (TBI) affects 2.5 million people annually within the United States alone, with over 300 000 severe injuries resulting in emergency room visits and hospital admissions. Severe TBI can result in long‐term disability. Posttraumatic epilepsy (PTE) is one of the most debilitating consequences of TBI, with an estimated incidence that ranges from 2% to 50% based on severity of injury. Conducting studies of PTE poses many challenges, because many subjects with TBI never develop epilepsy, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…205 Advances in neuroimaging software that allow serial volumetric imaging should allow a more quantitative and detailed analysis of the initial TBI injury and volume changes over time with and without progenitor cell treatment. 201 This approach is already being used in the evaluation of post-traumatic epilepsy 206,207 and Alzheimer's disease. 208 Resting Finally, newer MRI approaches which allow imaging of inflammation could provide insights into the course and distribution of inflammation throughout the initial and secondary injuries with and without progenitor cell treatment in both TBI and SNHL.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…205 Advances in neuroimaging software that allow serial volumetric imaging should allow a more quantitative and detailed analysis of the initial TBI injury and volume changes over time with and without progenitor cell treatment. 201 This approach is already being used in the evaluation of post-traumatic epilepsy 206,207 and Alzheimer's disease. 208 Resting Finally, newer MRI approaches which allow imaging of inflammation could provide insights into the course and distribution of inflammation throughout the initial and secondary injuries with and without progenitor cell treatment in both TBI and SNHL.…”
Section: Future Directionsmentioning
confidence: 99%
“…Advances in neuroimaging software that allow serial volumetric imaging should allow a more quantitative and detailed analysis of the initial TBI injury and volume changes over time with and without progenitor cell treatment 201 . This approach is already being used in the evaluation of post‐traumatic epilepsy 206,207 and Alzheimer's disease 208 . Resting state blood oxygen level dependent (BOLD) sequences and functional MRI (fMRI) have been used to analyze connectivity between various brain regions.…”
Section: Future Directionsmentioning
confidence: 99%
“… 6 Increasing computed tomography findings identify PTE outcomes 3–5 years following TBI: specially, 75% of patients with hemorrhagic contusions and related extracerebral hematoma had late PTE; only 16.7% of patients presenting intracerebral hemorrhage alone without extracerebral hematoma developed late seizures. 11 A recent pilot study further reported that lesions in the temporal lobe rather than overall injury severity were associated with the highest risk of PTE. 11 Brain blood barrier abnormalities predicting delayed, long-lasting seizures near the injured tissue are detectable on dynamic contrast-enhanced magnetic resonance imaging, gadolinium-enhanced T1, and T2-weighted fluid attenuated inversion recovery.…”
mentioning
confidence: 96%
“… 11 A recent pilot study further reported that lesions in the temporal lobe rather than overall injury severity were associated with the highest risk of PTE. 11 Brain blood barrier abnormalities predicting delayed, long-lasting seizures near the injured tissue are detectable on dynamic contrast-enhanced magnetic resonance imaging, gadolinium-enhanced T1, and T2-weighted fluid attenuated inversion recovery. 11 …”
mentioning
confidence: 96%
See 1 more Smart Citation